Fecundity and Oocyte size in the flyingfish (Cheilopogon arcticeps from Lanuza Bay, Surigao Del Sur - Belaza, Yeuclaire Dorothy Molina
The relationship of fecundity and oocyte diameter to body size and other reproductive aspects of the flying fish Cheilopogon arcticeps in Lanuza Bay were investigated in this study. Gravimetric method or weight method was used in order to estimate the fecundity of 35 mature female C. arcticeps ranging from 17.8-23.6 cm standard length. The total fecundity of C. arcticeps ranged from 1,123-41,684 while its oocyte diameter ranged from 0.8-3.6mm. the relationship of fecundity to standard length (SL) showed variable results and poor correlation. This may be indicative of a unique reproductive strategy of this species. Egg size to standard length showed an increasing trend but a weak correlation. In general smaller egg diameters were observed in smaller size class SL and bigger egg diameters appear in larger SL. The relationship of fecundity and gonad weight showed a positive linear correlation and increasing data. Thus as gonad weight increases, fecundity increases too. The correlation between fecundity and total length shows a weak relationship, however the correlation between fecundity and gonad weight show a stronger relationship. The present study aim to exhibit additional information on the rare documentation of flyingfish in the country